Study of Antinociceptive, Antipyretic and Neuropharmacological Activities of Leaf Extracts of Citrus assamensis (Bangladesh Pharmaceutical Journal, 2018)
The present study was executed to explore in vivo antinociceptive, antipyretic and neuropharmacological activities of different leaf extracts of Citrus assamensis in Swiss albino mice. C. assamensis leaf extract displayed marked dose dependent antinociceptive potential in the five pain models. All leaf extracts except chloroform (200 mg/kg body weight) extract, produced significant (**p